Co-design of output-based security control and dynamic event-triggered mechanism for NCSs under hybrid cyber attacks. Issue 11 (July 2022) - Zhang, Zhigang; Liu, Jinhai; Zhu, Hongfei; Zhang, Shuo; Liu, Xiuchong; Yu, Xue
Abstract: This paper investigates output-based dynamic event-triggered control for networked control systems (NCSs), in which hybrid cyber attacks randomly occur in communication network. First, a gain adjustable dynamic output feedback (DOF) controller is designed for NCSs and relaxes state-available constraint in presence of three types of attacks, including stochastic deception attacks, replay attacks and aperiodic denial-of-service (DoS) attacks. Second, a output-based dynamic event-triggered mechanism (DETM) is designed to optimize limited network resources under the cyber attacks. Third, a new switched system is established to describe the effect of hybrid cyber attacks, the DOF controller and the DETM simultaneously. Then, criteria for guaranteeing asymptotically stability of the switched system are obtained. Furthermore, the co-design method of DETM and DOF controller is provided to maintain the NCSs stability. Finally, an example is presented to show the effectiveness of the proposed methods in this paper.